Memorandum of Understanding between the International Livestock Research Institute (ILRI) and Ministry of Water and Energy - International Livestock Research Institute; Ministry of Water and Energy (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Memorandum of understanding (MOU) between the International Livestock Research Institute (ILRI) and Federal Ministry of Water and Energy of Ethiopia. MOU signed on March 11, 2022, by Jimmy Smith, Director-General of ILRI and Abraha Adugna, State Minister of Water and Energy.